simplify 4^13 ÷ 3^-5

1 answer

To simplify this expression, we can use the rule of exponents which states:

a^m ÷ a^n = a^(m - n)

Therefore, 4^13 ÷ 3^-5 can be simplified to:

4^13 ÷ 3^-5 = 4^13 × 3^5

Now, we can calculate the values:

4^13 = 67,108,864

3^5 = 243

Therefore, the simplified expression is:

67,108,864 × 243 = 16,302,983,872.
Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions